Characteristics of Food Raw Materials Made from Rubber Seeds Based on Variations in Soaking and Heating Times for Tempeh Production: Karakteristik Bahan Baku Pangan Berbahan Biji Karet Berdasarkan Variasi Lama Perendaman dan Pemanasan untuk Pembuatan Tempe - Habibie, Fadeli Muhammad; Simamora, Gervbry Ranti Ramadhani; Prayitno, Sutrisno Adi (jurnal makanan tropis dan teknologi agroindustri, 2025)
Rubber seeds (Hevea brasiliensis) have great potential as an alternative food source, particularly as a substitute ingredient in tempe production, due to their high protein and oil content. However, the presence of toxic hydrocyanic acid (HCN) remains a major obstacle to their utilization. This study aimed to investigate the effectiveness of soaking and heating processes in reducing HCN content and their effects on the nutritional composition of rubber seeds. A quantitative descriptive method with a Completely Randomized Design (CRD) was employed. The soaking treatment was applied for 0, 12, 24, and 36 hours, followed by two heating methods, namely steaming and boiling, each conducted for 30, 60, 90, and 120 minutes with three replications. HCN content was analyzed using spectrophotometry, with data processed using ANOVA and further tested with DMRT at a 5% significance level, while proximate analyses were analyzed descriptively. The results indicated that 24-hour soaking effectively reduced HCN levels to 0.14%, while heating for 120 minutes via steaming and boiling reduced HCN levels to 15.98 ppm and 14.21 ppm, respectively, below the safe consumption limit of 20 ppm. Proximate analysis showed no significant changes in the main nutritional components, although a slight decrease in fat and protein content was observed with longer heating durations. The study concluded that the combination of soaking and heating effectively reduced cyanide levels in rubber seeds without causing significant nutrient loss. Further research is recommended to explore fermentation processes, sensory characteristics, and food safety aspects of tempe made from rubber seeds as a local food diversification effort.